Wykonaj mnożenia...
np.(x+2y)*(y+3x)=x*y+x*3x+2y*y+2y*3x)=xy+3x²+2y²+6xy=7xy+3x²+2y²
a)(3-8x)*(3+8x)
b)(a-6)*(3a+4)
c)(xy+3y)*(4xy-5y)
d)(2x+3y)*(7x-4xy)
e)2x²y*(x-y)*(x+y)
f)3*(x-4)*(3x-2)
g)4*(2xy²+3yz)*(2xy²-3yz)
h)2*(3pq²-4)*(3pq²+4)

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T18:57:09+01:00
A)(3-8x)*(3+8x)= 9+24x-24x-64x= -64x+9
b)(a-6)*(3a+4)= 3a²+4a-18a-24=3a²-14a-24
c)(xy+3y)*(4xy-5y)= 4x²y²-5xy²+12xy²-15y²=4x²y²+7xy²-15y²
d)(2x+3y)*(7x-4xy)= 14x²-8x²y+21xy-12xy²
e)2x²y*(x-y)*(x+y)=2x²y (x²-y²)= 2x⁴y-2x²y³
f)3*(x-4)*(3x-2)=(3x-12)*(3x-2)= 9x²-6x-36x+24= 9x²-42x+24
g)4*(2xy²+3yz)*(2xy²-3yz)=4*(4x²y⁴-9y²z²)=16x²y⁴-369y²z²
h)2*(3pq²-4)*(3pq²+4)=2*(9p²q⁴-16)=18p²q⁴-32
2009-12-01T19:07:57+01:00
A) 9+24x-24x-64x²=-64+9
b) 3a²+4a-18a-25=3a²-25
c) 4x²y²-5xy²+12xy²-15y²=-15y²+4x²y²
d) 14x²-8x²y+21xy-12xy²
e) 2x³y²+x²-xy-xy-y²=2x y²+x²-y²
f) 3x-12+3x²-2x-12x-8=3x²
g) 8xy²+12yz+4x²y4-6xy³z+6xy³z-9y²z²=8xy²+12yz+4x²y4-9y²z²
h) 9pq²-8+9p²q4+12pq²-12pq²-8=-8+9p²q4


4 po literze q oznacza do potęgi 4
2009-12-01T19:13:27+01:00
A)(3-8x)*(3+8x)=3*3-8x*8x=9-64x²
b)(a-6)*(3a+4)=a*3a+a*4-6*3a-6*4=3a²+4a-18a-24=3a²-14a-24
c)(xy+3y)*(4xy-5y)=xy*4xy+xy*(-5y)+3y*4xy+3y*(-5y)=4xy²-5xy²+12xy²-15y²=11xy²-15y²
d)(2x+3y)*(7x-4xy)=2x*7x+2x*(-4xy)+3y*7x+3y*(-4xy)=14x²-8x²y+21xy-12xy²
e)2x²y*(x-y)*(x+y)=2x²y*(x*x-y*y)=2x²y*(x²-y²)=2x²y*x²+2x²y*(-y)=2x⁴-2xy³
f)3*(x-4)*(3x-2)=3*x+3*(-4)=3x-12
g)4*(2xy²+3yz)*(2xy²-3yz)=4*(4x²y⁴-9y²z²)=16x²y⁴-36y²z²
h)2*(3pq²-4)*(3pq²+4)=2*(9pq⁴-16)=18pq⁴-32